Lessons learned from articulating concrete block (ACB) field installations - Nadeau, J. A., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Articulating Concrete Blocks (ACBs) have been a popular choice for high performance erosion control applications and shoreline revetments for well over 35 years and continue to grow in popularity. Estimates point to over 200 dam embankments and emergency spillways having been armored with ACBs in the past 30 years. As a result of these applications, as well as the thousands of other projects not specific to dams, much has been learned from a theoretical as well as practical application standpoint of properly utilizing ACBs in the field. This presentation will provide information concerning ACB Factor of Safety (FOS) determination, briefly review the ACB testing protocols and data analysis, and discuss the practical uses and limitations of ACB applications. New installation techniques that show promise for improving ACB performance will be discussed. ACBs are a proven cost effective erosion countermeasure, however experience and attention to detail during the design and installation of systems is of paramount importance for expected performance.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: ACB; erosion control applications; embankment; emergency spillways; cost effective